1994
DOI: 10.1111/j.1365-3091.1994.tb01453.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity of biogenic carbonate particles in microbial mats

Abstract: Non-skeletal carbonate particles in microbial mats were studied using thin sections and scanning electron microscopy. The microbial mats form biolaminated units (so-called potential stromatolites) in salterns. This study emphasizes the coexistence of different particle forms and makes a genetic connection between the heterogeneity of the organic substrate built by bacteria and diatoms and their extracellular polymeric substances (EPS). Whereas allochthonous particles are scarce, Lanzarote microbial mats provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 45 publications
3
59
0
Order By: Relevance
“…These chemicals were found to be trapped in the mineral matrices of the buildings. An investigation of the coexistence of dif- ferent particle forms of biogenic calcium carbonate deposits within the microbial biofilm was investigated by Gerdes et al (1994), who showed that aragonite accumulation occurs due to biologically induced physiochemical changes in the microenvironment of the interface. Hydration-dehydration cycles might exert a clear biogeophysical effect on the stone.…”
Section: Interaction Between Weathering Agents Elemental Compositionmentioning
confidence: 99%
“…These chemicals were found to be trapped in the mineral matrices of the buildings. An investigation of the coexistence of dif- ferent particle forms of biogenic calcium carbonate deposits within the microbial biofilm was investigated by Gerdes et al (1994), who showed that aragonite accumulation occurs due to biologically induced physiochemical changes in the microenvironment of the interface. Hydration-dehydration cycles might exert a clear biogeophysical effect on the stone.…”
Section: Interaction Between Weathering Agents Elemental Compositionmentioning
confidence: 99%
“…130/3. 1 Microbial peloids. The clotted structure of the peloids and the occurrence as constituents of bindstones point to a microbially induced origin of the grains formed in situ within mats ('benthic peloids': Gerdes et al 1994;Kazmierczak et al 1996). Bedded lagoonal limestone.…”
Section: Plate 10 Peloids and Cortoidsmentioning
confidence: 98%
“…In-situ growth of modern oncoids has been reported from lakes, lake margins and sabkhas (Jones and Wilkinson 1978), and rivers or streams (Freytet and Plaziat 1965; Hartkopf-Fröder et al 1989). Ancient in situ growth has been claimed for Tertiary lacustrine oncoids (Leinfelder and Hartkopf-Fröder 1990).Algal and cyanobacterial pellets formed in situ (benthic peloids) occur in microbial mats of salinas, saline lakes and intertidal settings (Gerdes et al 1994; Kazmierczak et al 1996). The rounded micritic grains as well as autochthonous micrite (Sect.…”
mentioning
confidence: 96%
See 2 more Smart Citations